Semen characteristics of Colossoma macropomum from three successive sample collections in the same reproductive cycle - Pires, Luana Barbosa; Sanches, Eduardo Antonio [UNESP]; Romagosa, Elizabeth [UNESP]; Corrêa Filho, Ruy Alberto Caetano; Streit Junior, Danilo Pedro; Nass, Rosiane Araujo Rodrigues; Povh, Jayme Aparecido (Hindawi, 2017)
The objective of this work was to evaluate the semen characteristics of C. macropomum fish from three successive semen sample collections taken during the same reproductive cycle. Six breeders (6.4 ± 1.5 kg) induced with crude carp pituitary extract (2.5 mg kg−1) were used. Samples of semen were collected in graduated syringes after a period of 260 degree-hours. The semen was collected from the same males in September 2014 (sample 1), December 2014 (64 days after the first collection – sample 2) and February 2015 (86 days after the second collection – sample 3). The semen volume was higher (P < 0.05) in the sample 1 (6.7 mL) and sample 2 (3.4 mL) than in the sample 3 (1.0 mL). Sperm concentration and normal sperm did not significantly differ between samples. Likewise, sperm motility, curvilinear velocity, displacement velocity, oscillation and beat cross frequency did not vary, whereas straight-line velocity, straightness and progression were higher (P < 0.05) in sample 2 (December). In general, despite lower amounts, the semen appeared to be of good quality for all three samples collected during the same reproductive period.
Keywords: aquaculture; induced reproduction; rheophilic fish; sperm production; tambaqui